2018
DOI: 10.3389/fmicb.2018.00380
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of cDNA Dataset to Investigate Possible Association of Differentially Expressed Genes of Human THP1-Monocytic Cells in Cancer Progression Affected by Bacterial Shiga Toxins

Abstract: Shiga toxin (Stxs) is a family of structurally and functionally related bacterial cytotoxins produced by Shigella dysenteriae serotype 1 and shigatoxigenic group of Escherichia coli that cause shigellosis and hemorrhagic colitis, respectively. Until recently, it has been thought that Stxs only inhibits the protein synthesis and induces expression to a limited number of genes in host cells, but recent data showed that Stxs can trigger several signaling pathways in mammalian cells and activate cell cycle and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“…Marino et al demonstrated that OAS1 was able to affect cell migration [28]. Moreover, OASL was considerably related to cancer proliferation [26]. Our data highlighted the prognostic values of OAS members in mRNA expression and DNA methylation, as well as the gene signature, enabling multilevel insights for these prognostic predictors.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Marino et al demonstrated that OAS1 was able to affect cell migration [28]. Moreover, OASL was considerably related to cancer proliferation [26]. Our data highlighted the prognostic values of OAS members in mRNA expression and DNA methylation, as well as the gene signature, enabling multilevel insights for these prognostic predictors.…”
Section: Discussionsupporting
confidence: 60%
“…Previously, OAS family members have been found to be involved in a variety of diseases, including infections, autoimmune disorders and cancer. Their functions include antiviral modulation, apoptosis control, cell growth, differentiation and gene regulation [19][20][21][22][23][24][25][26]. In 1986, Liu et al reported a potential correlation between OAS activity and tumor growth in human mammary tumors [27].…”
Section: Discussionmentioning
confidence: 99%
“…The OAS families, of which OASL is a member, have been found correlated with multiple diseases, including infections, autoimmune disorders, and cancers (22)(23)(24). In particular, it has been reported that OASL is significantly related to tumor proliferation (10). Our data highlighted the prognostic value and therapeutic target of OASL in PDCA.…”
Section: Discussionsupporting
confidence: 58%
“…The role of OASL in tumor itself is rarely reported. Studies have shown that OASL is closely related to the proliferation of various tumors (10). In addition, OASL has been identified as a pivotal gene of trastuzumab-resistant gastric cancer (11).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, group IB introns accounted for 57.4% of total introns (70/122). Interestingly, the 13th intron of P. noxius cox1 gene (cox1_intron13) was predicted to have two separated complete intron cores (IB and ID) suggesting a twintron: an intron inserted by another intron (Deng et al. 2018).…”
Section: Resultsmentioning
confidence: 99%